(31345) 1998 PG: A BINARY NEAR-EARTH ASTEROID? - Warner, Brian D; Pravec, Petr; Macías, Amadeo Aznar; Benishek, Vladimir; Casanova, Victor; Oey, Julian; Pray, Donald P (The Minor planet bulletin, 2019)
Photometric observations of the near-Earth asteroid (31345) 1998 PG by Pravec et al. (2000) found a rotation period of 2.51620 h. Also found was a secondary period of 7.0035 h, or the double-period of 14.007 h, possibly indicating an additional body in the system. An extended campaign by the authors in 2018 lead to a similar primary period of 2.5168 h. However, instead of a 7-hour secondary period, one of about 16 hours was found with the lightcurve showing apparent mutual events (occultations and/or eclipses). The data sets from 1998 and 2018 could not be fit to a secondary period near the one found at the opposing apparition. The conclusion is that the asteroid is very likely binary, but - other than the primary rotation period - the system's parameters are ill-defined and only future observations will sufficiently refine them.